Assessment in First Year University: A Model to Manage Transition - Taylor, J. (Journal of University Teaching and Learning Practice, 2008)
For most students assessment guides their study and learning practice. Yet in the literature associated with the first year of study at university, few have mobilised the power of assessment to develop and engage first year undergraduate students. This paper presents a model of assessment for first year students which separates the semester into three overlapping assessment phases: assessment for transition, assessment for development and assessment for achievement. The implementation and usefulness of the model is supported by examples from mathematics, engineering, computing, communication and nursing studies at the University of Southern Queensland (USQ). Particular attention is paid to assessments for transition which occur early in the semester and are linked more closely with processes than specific content. Evidence is collated on the success of assessments in improving the participation of students, especially distance education students.